Kepemimpinan Profetik dalam Manajemen Pendidikan bagi Pemimpin Masa Depan - Fatimah, Rosyada Ayu; Setiawan, Farid; Tajuddin, Muhammad Afif Nur (ANWARUL, 2022)
The complexity of the situation and the challenges faced by the Indonesian nation and state recently, require strong national leadership in all fields. Indonesian psychological scientists and psychologists are expected to play an active role in taking part in strengthening national leadership. One of the efforts, among others, has been carried out by Budiharto & Himam (2006) who conducted a study in the form of preparing theoretical constructs and measuring prophetic leadership, namely the concept of leadership based on the moral and spiritual values of the Muslim community in Indonesia. The results of this study have been used as a reference for government and business organizations in Indonesia in choosing leaders, as well as equipping their leaders with prophetic moral values. Further research has been conducted, among others, regarding the relationship between prophetic leadership and work motivation, job satisfaction, organizational commitment, and organizational citizenship behavior of employees in several organizations and regions in Indonesia. Assessment of prophetic leadership was carried out as one of the fit and proper test methods for rector candidates of a private university in 2008 and 2013, candidates for directors of private hospitals in 2009, and candidates for officials in a ministry in 2014. Psychological intervention using prophetic leadership has also been done. Andansari et al (2010) concluded that prophetic leadership training can improve problem solving skills of employees of Islamic financial services cooperatives in Central Java. Alawiyah et al (2012) found that prophetic leadership training can increase the teaching commitment of the "H" Integrated Islamic Elementary School teachers in Yogyakarta. Kuswanto and Rasyid (2013) found that prophetic leadership training can improve the managerial ability of employees of Islamic financial services cooperatives in the Special Region of Yogyakarta. Kumolohadi and Budiharto (2013) concluded that prophetic leadership counseling can improve the anti-corruption character of Regional Government X officials.